A Subtitling Analysis Of Interrogative Sentence On Thor 2: The Darkworld Movie - Wibowo, Novian Adi; , Dr. Anam Sutopo, M.Hum; , Siti Fatimah, S. Pd, M. Hum (2015)
This study aims at describing the subtitling analysis of interrogative sentences on Thor 2: The Dark World movie, classifying the types of interrogative sentence found in Thor 2: The Dark World movie and describing the equivalent of the subtitle. The type of this research is descriptive qualitative research. In collecting data, the writer uses note taking. The data are analyzed using theory based on types of interrogative sentence by Greenbaum (2002:121). There are steps of collecting data, namely: watching the film, reading the movie script the movie, underlying the interrogative sentence in the movie, coding the data of interrogative sentence. The collected data are analyzed using theory based on types of interrogative sentence by Greenbaum. The result of the research show that the writer found 182 data of interrogative sentences on Thor 2: The Dark World movie. The writer classify 182 data of interrogative sentences into five types of interrogative sentence. There are 78 or 42.8% data belongs to wh question, 60 or 33.1% belongs to yes no question, 05 or 2.7% data belongs to question tag, 02 or 1.1% data belongs to alternative question, 37 or 20.3% data belongs to declarative question. From 182 data of interrogative sentences, the writer found interrogative sentence that are equivalent and non-equivalent translation. There are 167 or 91.7% data are equivalent subtitle and 15 or 8.3% data are non-equivalent subtitle. It is means that the translator make a good translation, because 167 or 91.7% data are equivalent.